Pemanfaatan Kitin Udang Sebagai Penyerap Timbal dan Tembaga pada Limbah Cair Industri Batik di Solo - Cahyanto, Martinus Dwi; Aida, Yuniarti; Pranata, F. Sinung (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2008)
The waste of shrimps in the form of skin, head, and tail that is disposed from shrimp processing and disposal are usually thrown away with out being processed, therefore the wastes may cause environmental pollution, especially from the unpleasant stench. Shrimp wastes contain compounds called chitin and can be utilized to absorb heavy metals which are mainly from industrial wastes. The batik industries in Solo usually utilize synthetic colors, because synthetic colors are cheaper and can make the products look more satisfying. Nevertheless, the liquid wastes from these batik industries are usually still colorful when it is disposed and are usually hard to be degraded by nature. Moreover, these wates contains heavy metals such as lead (Pb) and copper (Cu) that can endanger the human health. This research is conducted in order to notify the performance of chitin in order to absorb heavy metals such as lead (Pb) and copper (Cu). There are five treatments that is conducted in this research by adding chitin powder as much as 0 g (control), 1, 2, 3 and 4 g into the sample of batik liquid wastes. The lead (Pb) and copper (Cu) substance of the sample will then be measured using the AAS (Atomic Absorption Spectrophotometer), then the lead (Pb) and copper (Cu) substance of each treatment will be compared with the control. The result of the research shows that chitin can reduce the content of lead and copper in batik liquid wastes. Based on the research result, it is concluded that the addition of 4 g of chitin powder into the sample of batik liquid wastes can give the most maximum result, i.e. the reduction of the Pb content by 6.138 ppm from the control of 17.773 ppm into 11,635 ppm, and the reduction of the Cu content by 3.779 ppm from the control of 7.903 ppm into 4.104 ppm.